Politik Hukum Syarak Terhadap Perbudakan - Sholihin Siregar, Ahmad (Al Mabhats : Jurnal Penelitian Sosial Agama, 2018)
Slavery has been a part of human civilization, acknowledge since before century to the modern era. This article purposes to describe the policy of Islamic las, as a social control and a tool of social engineering, in dealing with slavery. Islamic law gives the most of its attention to liberation of slaves. It widely open the door of liberation, encourages muslim to liberate slaves through general righteousness, contract (mukatabah), birth, testament, kinship, persecutioan, tabd`idh, penalty and islamity. In short, the policy of Islamic law porpuses to restrict the source of slavery, restore slaves social status in social and personal lives and liberate human from the slavery.